PENGARUH KONSENTRASI RAGI TERHADAP BIOETANOL BUAH SUKUN (Artocarpus altilis) SEBAGAI PENGEMBANGAN LKPD PEMBELAJARAN MATERI BIOTEKNOLOGI SMA KELAS XII - Sri Rahayu; Imam Mahadi; Irda Sayuti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: The research aims to know influence of yeast concentration sukun (Artocarpus altilis) bioethanol level and produce a design biology student worksheet at senior high school biotechnology material. Experimental research by conducted experiment for 9%, 10%, 11%, 12% and 13% of sukun with 5 treatments 3 replicates whewe the substrate was hudrolyzed first with 5% sulfuric acid and continued with the developments of student worksheet from experimental research (only analyze and design stages). The research data were analized using variances analysis techniques and continued with Duncan’s Multiple Range Test (DMRT) of the 5% level. The results of the study indicate that yeast concentration affects the bioethanol. The highest average bioethanol content was found at 11% which was 9.70%. All research data can be used to design senior high school biology student worksheet in conventional biotechnology material class XII with project based learning models. However, before the worksheet design is used on a wider scale it is recomended that a feasibility test and effectiveness be carried out on a limited scale.Key Words: Yeast Concentration, Artocarpus altilis, Bioethanol, Student Worksheet Desain